Tax Effects of Operating as a Corporation or Partnership (Book). - Holzman, Robert S. (The Accounting Review, 1958)
Reviews the book "Tax Effects of Operating as a Corporation or Partnership," by Houstin Shockey and Henry W. Sweeney.